Impact of Exclusive English Language Use in Physiology Lecture on Students Physiology Learning in Bangladesh - Khan, Mohammad Uzire Azam; Abedin, Mohammad Mohaimenul (Journal of Bangladesh Society of Physiologist, 2017)
Background: Medical students of Bangladesh have to encounter English as learning media. But teachers often do not use English exclusively in their lectures thinking that students may not understand English clearly. Objective: To assess the impact of exclusive use of English language in physiology lectures on students learning. Method: This comparative study was conducted in the Department of Physiology, Abdul Malek Ukil Medical College, Noakhali, Bangladesh during January November, 2013. One hundred and sixteen first year MBBS students of two sessions of a government medical college were enrolled for the study by purposive sampling. Exclusive English was used in physiology lectures of 1st term course for the students of 2012-2013 session (group EE) and mixed Bengali and English was used to teach the students of 2011-2012 session (group BE). First term examination results were compared by Students t test and Chi-square test as applicable. Result: The students of EE obtained significantly higher mean marks both in written (p<0.001) and oral (p<0.001) examinations than those of group BE. However there was no significant difference between groups in pass rate (p>0.05)). Conclusion: The students who attended the lectures with exclusive English obtained better marks in individual component of assessment than the students who attended the lectures with mixed Bengali and English. However, English language use in teaching showed no effect on the pass rate. Bangladesh Soc Physiol. 2017, June; 12(1): 28-32